Study of Darlington Pair Amplifier with Matched N-Channel MOSFETs - Shukla, Sachchida Nand (New Approaches in Engineering Research Vol. 9, 2021)
Two different circuit models of small-signal amplifiers are developed using PSpice-defined identical N-channel commercial power MOSFETs in Darlington pair topology. Proposed circuits are also tested with the user-defined PSpice models of matched N-channel MOSFETs. Respective amplifiers successfully eliminate the poor frequency response problem of Darlington pair amplifiers at higher frequencies. An additional biasing resistance RA, ranging from 1K\(Ω\) to 100K\(Ω\), is to be essentially used in the proposed circuits to maintain their voltage/current amplification property. In presence of RA, respective amplifiers crop high voltage gains, moderate range bandwidths and significantly high current gains for 1-10mV input signal range at 1 KHz frequency. Both the proposed amplifier circuits can be tuned in the specific audible frequency range, extending approximately from 130Hz to 55KHz. Tuning performance makes these amplifier circuits suitable to use in Radio and TV receivers. The qualitative and tuning performance offers a flexible application to these amplifiers to be used as high voltage gain, high power gain and tuned amplifiers. Effect of environmental temperature, phase variation at different operation frequencies, AC equivalent circuit analysis and effect of variation in biasing resistances are prominently discussed for the proposed amplifiers.